Sanksi Hukum Terhadap Pelaku Pembajakan Film Melalui Website Ilegal - I Gusti Ngurah Ketut Satya Wicaksana; Anak Agung Sagung Laksmi Dewi; Indah Permatasari (Jurnal Analogi Hukum, 2025)
Indonesia there are laws and regulations governing copyright and protection of holders, in the criminal code in law number 28 of 2014 on copyright, based on the background described, the formulation of the problem to be studied as follows: (1) How is the legal regulation of movie piracy through illegal websites? (2) How are the legal sanctions against the perpetrators of movie piracy in illegal websites? The research method is important so that the research objectives can be achieved optimally, this research examines the study in a normative law way, in writing this thesis there is a case approach, and the approach of legislation, and concept approach. The results of the study state that the legal arrangements for perpetrators of film piracy, film piracy is the unauthorized duplication of creations and related rights products for economic gain, regulated in Article 113 of Law 28 of 2014 concerning Copyright, in the legal regulation of films regulates piracy as regulated in Article 80 of Law 33 of 2009 concerning cinema. Suggestions for the government to provide protection for film creators, especially in Indonesia through laws and policies, for the public, are expected not to access illegal websites or illegal films.